A rare case of fructose-1, 6-bisphosphatase deficiency: Clinical features in a pediatric patient - Shami Pokhrel; Subha Sainju; Prasanna Lamsal; Uma Devi Chhetri (Molecular Genetics and Metabolism Reports)
Fructose-1, 6- bisphosphatase deficiency is a rare autosomal recessive inborn error of fructose metabolism which mainly affects gluconeogenesis. It often presents with ketotic hypoglycemia and lactic acidosis, with hyperventilation. The disease has a high mortality rate when undiagnosed.Here we report a case of this rare disorder, referred to our hospital in Western Nepal, diagnosed originally as pneumonia. The patient presented in respiratory distress with severe metabolic acidosis and dehydration. She also demonstrated hypoglycemia, hypernatremia, coagulation dysfunction and albuminuria, all of which gradually improved, though her lactate remained consistently elevated. This led to investigation of urinary ketones which were positive suggesting a defect in the metabolism of carbohydrates. Urine organic acid profile and whole exome sequencing finally confirmed the diagnosis of Fructose-1, 6- bisphosphatase deficiency. To our knowledge this is the first case report of this disease diagnosed in Nepal.